Students’ Perception of Using Podcast Toward English Speaking Ability at Students of English Department UINFAS Bengkulu - Ani Sartika; Fera Zasrianita; Hanura Febriani (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This study explores students’ perceptions of using podcasts as a tool to enhance English speaking skills among fourth-semester students at UIN Fatmawati Sukarno Bengkulu. Employing a qualitative descriptive method, data were collected through questionnaires and interviews. The findings reveal that students have generally positive perceptions of podcasts due to their accessibility, authenticity, and flexibility. Podcasts are perceived to contribute significantly to speaking development, particularly in pronunciation, vocabulary, intonation, and confidence. Many students find podcasts more engaging than traditional materials and appreciate the opportunity to listen to native speakers in natural contexts. However, the study also identifies challenges, including difficulties in understanding accents, lack of visuals, and limited access for some students. Although podcasts are not consistently integrated into formal instruction, students report that regular podcast usage improves their speaking fluency and reduces anxiety. The study concludes that podcasts are effective and enjoyable learning tools, but their implementation should be adapted to individual learning preferences and supported by other resources. The results suggest that podcasts hold great potential in technology-integrated language learning and should be more systematically utilized in EFL classrooms.